RESEARCH ON THE OPTIMIZATION OF THE TECHNICAL AND TACTICAL SYSTEM OF MARTIAL ARTS SHORT-SOLDIER SPORTS AND THE TRAINING PATH OF HIGH-LEVEL ATHLETES - WANG FENG, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: As an emerging project that combines traditional Chinese martial arts with modern competitive sports, martial arts short-soldier sports are both practical, ornamental and competitive.With the continuous improvement of the rules of martial arts short-handed competition and the continuous improvement of the level of competitions, it is difficult for the traditional technical and tactical system to fully adapt to the needs of high-level competition, and the training of high-level athletes is also facing the problem of insufficient systematization.On the basis of combing the current situation of the development of martial arts short-handed sports skills and tactics, this paper analyzes the main problems in the current use of skills and tactics, discusses the basic principles and implementation paths of the optimization of the skills and tactics system, and proposes a scientific path for the training of high-level athletes from the aspects of training concept, material selection mechanism, competition practice and guarantee system.The research believes that building a systematic, practical and scientific technical and tactical system is the key to improving the competitive level of martial arts short soldiers and promoting the training of high-level athletes.